2020
DOI: 10.3390/ijerph17072203
|View full text |Cite
|
Sign up to set email alerts
|

Provincial Correctional Service Workers: The Prevalence of Mental Disorders

Abstract: Correctional service employees in Ontario, Canada (n = 1487) began an online survey available from 2017 to 2018 designed to assess the prevalence and correlates of mental health challenges. Participants who provided data for the current study (n = 1032) included provincial staff working in institutional wellness (e.g., nurses) (n = 71), training (e.g., program officers) (n = 26), governance (e.g., superintendents) (n = 82), correctional officers (n = 553), administration (e.g., record keeping) (n = 25), and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
71
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 58 publications
(82 citation statements)
references
References 41 publications
6
71
0
5
Order By: Relevance
“…Such organizational stresses can impact staff well-being (Ricciardelli, 2018; Carleton et al, 2020 ). Participant 289, a casual or fixed-term male CO, explained some challenges with working in a casual position:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such organizational stresses can impact staff well-being (Ricciardelli, 2018; Carleton et al, 2020 ). Participant 289, a casual or fixed-term male CO, explained some challenges with working in a casual position:…”
Section: Resultsmentioning
confidence: 99%
“…The current article data emerged as part of the mental health and well-being study , designed to begin to assess the prevalence of mental health challenges and mental disorders among correctional staff working in all areas of correctional employment (e.g., institutional, community, and administrative corrections) (for more information about the larger study, see Carleton et al, 2020 ). Employees of correctional services in Ontario were asked to complete an anonymous and confidential online survey from December 8, 2017 to June 30, 2018.…”
Section: Methodsmentioning
confidence: 99%
“…Research on CW psychological well-being commonly operationalizes the outcome as job stress, the “psychological strain leading to job-related hardness, tension, anxiety, frustration, and worry arising from work” [ 8 ] (p. 23); however, recent research is increasingly focused on symptoms of Posttraumatic Stress Disorder (PTSD), Major Depressive Disorder (MDD), and Generalized Anxiety Disorder (GAD) as common psychological outcomes associated with exposure to potentially psychologically traumatic events (PPTEs) [ 9 ] within correctional services work [ 6 , 10 , 11 , 12 ]. Early research demonstrates that the Canadian prevalence of mental health disorders among CWs is higher than other public safety personnel (PSP) groups [ 13 , 14 ]. The available evidence suggests that occupational stressors (i.e., operational stressors related to job content; organizational stressors related to job context) may be as impactful on PSP psychological well-being as exposure to PPTEs [ 15 ], but results specific to CWs remain sparse (for a discussion of organizational and operational stress with the policing context see Duxbury and Higgins, 2001; 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The current study data were drawn from a larger research project examining CW well-being. The design details are presented elsewhere [ 27 , 30 , 31 ]; in short, cross-sectional data were collected via an online survey available from 8 December 2017 to 30 June 2018 based on established guidelines for web-based surveys [ 32 ]. CWs in the Ontario provincial correctional system were invited by email to answer socio-demographic questions, respond to self-report scales assessing the presence of different symptoms, and provide commentary in response to open-ended items.…”
Section: Methodsmentioning
confidence: 99%
“…Drawing from the same dataset as the current study, Carleton and colleagues found that provincial CWs further evidenced high levels of mental disorders, with 58.2% screening positive for one or more mental disorders (i.e., major depressive disorder, PTSD, generalised anxiety disorder) [ 27 ]. In addition, CWs further reported high levels of past-year and lifetime suicidal thoughts (i.e., 7.0%; 26.6%), planning (i.e., 2.6%; 11.9%), and attempts (i.e., n/a; 5.2%) [ 28 ].…”
Section: Introductionmentioning
confidence: 99%